The Benefits of Strategic Entrepreneurship: A case study of Habitual Entrepreneurs - Watkins, Jason (2009)
This management project aims to address the benefits of applying the concept of Strategic Entrepreneurship from the experience of habitual entrepreneurs. Of special concern will be the connection between possessing an entrepreneurial mindset and providing entrepreneurial leadership and culture in the search for new opportunities and the creation of continuous innovation. The opportunity-seeking behaviour of both portfolio and serial entrepreneurs will be examined closely and any learning curve effects deriving from previous business-ownership will be assessed. Of special interest will be the question how habitual entrepreneurs strike the balance between exploiting their current business(es) and exploring for new opportunities. We also want to discover whether the benefits of Strategic Entrepreneurship can ease the transition from being novice entrepreneur to becoming an habitual entrepreneur.